Digital Maternal Health Interventions for Preeclampsia Prevention, Early Detection, and Maternal Mental Health Support: A Systematic Review and Meta-Analysis - lis Indriayani; Thika Marliana; Umi Kalsum; Lia Octavia (Journal of Scientific Insights, 2026)
Background: Preeclampsia remains a preventable cause of maternal and perinatal morbidity and mortality, particularly when delayed recognition, low maternal health literacy, poor adherence to preventive recommendations, and psychological distress delay emergency care-seeking. Digital maternal health interventions, including smartphone applications, telehealth, mHealth-supported community screening, remote blood-pressure monitoring, and digital education, may strengthen preeclampsia prevention and early detection. Objective: This systematic review and meta-analysis synthesized evidence on digital maternal health interventions for preeclampsia prevention, early detection, and maternal mental-health support. Methods: A PRISMA 2020-guided review was conducted using uploaded full-text articles representing digital maternal health interventions related to preeclampsia, gestational hypertension, eclampsia prevention, antenatal risk communication, or pregnancy danger-sign awareness. Study characteristics, intervention components, outcomes, and risk of bias were extracted. Hedges g was calculated for comparative studies with extractable mean and standard deviation data. Random-effects pooling used the DerSimonian-Laird method. Results: Ten full-text records were assessed. Seven primary studies were retained for qualitative synthesis, while three studies with compatible continuous outcomes were included in quantitative pooling. Digital interventions improved maternal knowledge, danger-sign awareness, preventive adherence, and monitoring engagement. The random-effects pooled Hedges g was 1.21 (95% CI 0.20 to 2.21), indicating a large favorable effect but with substantial heterogeneity (I2=95.0%; tau2=0.74). Funnel-plot and Egger-test interpretation was limited because only three studies were quantitatively pooled. Conclusion: Digital maternal health interventions show promising benefits for preeclampsia-related knowledge, preventive behavior, monitoring engagement, and psychological reassurance. However, current evidence remains heterogeneous and requires more standardized RCTs with validated outcomes and complete mean-SD reporting.